Business Administration Students in Five Canadian Universities: A Study of Values - Hurka, Slavek J. (Canadian Journal of Higher Education, 1980)
Using the Allport-Vernon-Lindzey (A VL ) for measuring dominant values, 513 business administration students from five schools in the Prairie Region were tested. The A VL scale measures relative importance of student values in six basic areas: theoretical, econo- mic, aesthetic, social, political and religious. The sample included 349 men and 164 women enrolled in different class levels (years 1 to 4) in five schools of business. Significant differences were found between business student values and the norms for the general college population, and between the values of male and female business adminis- tration students. Differences were progressively less significant when business students were compared by class levels and by schools.